DINAMIKA GERAK DAN ROTASI BUMI DALAM AL-QUR’AN: STUDI SAINS EKSEGETIS PERSPEKTIF ALI ASH-SHABUNI - Anas Maulana Abdillah; Siti Nurhalijah; Muhammad Ghufron; Malik Subkan; Andi Rosa (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2026)
This study discusses the dynamics of the earth’s motion and rotation in the Qur’an through the perspective of Ali Ash-Shabuni’s exegetical science approach. This research is motivated by the development of scientific interpretation (tafsir ‘ilmi) which seeks to integrate kauniyah verses with modern scientific findings, particularly in the fields of astronomy and geology. The study aims to analyze the epistemology of Ali Ash-Shabuni’s interpretation and explain the relevance of his interpretation to the phenomena of the earth’s motion and rotation based on modern science. The method employed is qualitative research based on library research using a descriptive-analytical approach. The primary data sources are Ali Ash-Shabuni’s works, especially Ḥarakat al-Arḍ wa Daurānuhā and Gerak dan Rotasi Bumi: Realitas Ilmiah dalam Al-Qur’an, while secondary data were obtained from various literature on Qur’anic exegesis, astronomy, and Islamic science. The findings reveal that Ali Ash-Shabuni combines the tafsir bi al-ma’ṡūr approach with rational and scientific analysis in interpreting kauniyah verses. His interpretation of Q.S. Az-Zumar [39]: 5, Q.S. Al-Anbiya’ [21]: 33, Q.S. Yasin [36]: 40, and Q.S. An-Naml [27]: 88 demonstrates a harmony between the Qur’an and modern science regarding the earth’s rotation, the movement of celestial bodies, and the function of mountains in maintaining the earth’s stability. This study confirms that Ash-Shabuni’s exegetical scientific approach does not position the Qur’an as a technical science textbook, but rather as a source of guidance that encourages humanity to understand the order of the universe as a manifestation of Allah’s power.